086: RESILIENCE STRATEGIES OF FILIPINO FAMILY FARMERS: ENSURING FOOD AVAILABILITY DURING EL NIÑO PHENOMENON FROM 2008–2013. (24th August 2015) - Conopio, Andrea Pitahin; Alviar, Czarina Sambale; Ramos, Angelene Baruk
Abstract : Background: Philippines experiences different kinds of natural calamities and one commonly known extreme weather events is the El Niño phenomenon. Drought, considered as a challenge faced by Family Farmers in the country, is commonly endured problem in Sitio Madlum in Brgy. Sibul Springs, San Miguel, Bulacan in ensuring the availability of food. Objectives: In this study, the resilience strategies of Filipino Farmers in ensuring food availability during El Niño phenomenon will be identified. Methods: The family farmers and the barangay officials, chosen through homogenous sampling technique, will help determine the socio-economic profile of the community and will also serve as the key informants for the study. Using the extreme case sampling, 6 family farmers from 30 family farmers who answered the survey will be interviewed further for the case study. The results, together with the observations of the researchers, will be analyzed through Ika Darnhofer' s Resilience Thinking Approach. Result: The expected outcome of the study will show that the family farmers will diversify crops; seek assistance from different NGOs, LGUs and the organizations that they belong to; engage in different jobs; apply different techniques instructed by International Rice Research Institute; and gain support from their relatives. Conclusion: This study will identify how the resilience strategies of the family farmers contribute not just for ensuring the availabilty of food but also in attaining sustainable development for the community.